2008
DOI: 10.1007/s11999-008-0224-5
|View full text |Cite
|
Sign up to set email alerts
|

High Association of Posterior Malleolus Fractures with Spiral Distal Tibial Fractures

Abstract: Associations between fracture patterns are important and can ensure proper diagnosis and guide treatment. Occult posterior malleolus fractures associated with distal spiral tibia fractures often are underrecognized and the morbidity of a missed posterior malleolus injury can be substantial. We determined the association between the two injuries and evaluated the ability of a new protocol to improve management of these associated fractures. Of 62 consecutive patients with fractures of the distal third of the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 15 publications
2
37
0
4
Order By: Relevance
“…Two recent studies utilizing CT imaging to evaluate for concomitant ankle fractures demonstrated a higher incidence of injury ranging from 39–43%. 8,10 However, both of these studies limited their investigation to distal one-third diaphyseal tibia fractures. Our results indicate that concomitant articular ankle injuries are more common than previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies utilizing CT imaging to evaluate for concomitant ankle fractures demonstrated a higher incidence of injury ranging from 39–43%. 8,10 However, both of these studies limited their investigation to distal one-third diaphyseal tibia fractures. Our results indicate that concomitant articular ankle injuries are more common than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although distal one-third spiral tibial shaft fractures have been shown to have a strong association with concomitant ankle fractures, no publication has explicitly quantified the predictive ability of this, or other, radiographic fracture patterns. 810 Therefore, our hypothesis for this study is twofold: 1) the incidence of concomitant ankle injuries and tibial shaft fractures is underappreciated and is higher than previously reported; and 2) common radiographic characteristics such as location and pattern of the tibial and fibular shaft fractures exist that can quantitatively predict the presence or absence of an ankle injury.…”
Section: Introductionmentioning
confidence: 95%
“…[25][26][27] Distal third tibial shaft fracture location, spiral type fracture pattern, or an associated spiral fibula fracture is predictive of an intraarticular component. [25][26][27] Distal third tibial shaft fracture location, spiral type fracture pattern, or an associated spiral fibula fracture is predictive of an intraarticular component.…”
Section: Do Not Miss the "Other" Fracturementioning
confidence: 99%
“…Tibial fractures are the most common long bone fractures [2], while distal tibail fractures are even more complicated due to its proximity to ankle, and the close relationship with thin soft tissue envelope and severe comminution [3e5]. Additionally, distal tibial fractures are associated with posterior malleolus fractures [6].…”
Section: Introductionmentioning
confidence: 99%